KONVERGENSI MEDIA SURAT KABAR LOKAL KALTENG POS: Media Convergence of Local Newspapers Kalteng Pos - Muhammad Iqbal Rizaldy; Eni Maryani; Purwanti Hadisiwi; Pandan Yudhapramesti (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The development of technology, information, and communication requires print media specifically for local newspaper to keep up with the development of the digital era by conducting media convergence, the same thing was done by the local newspaper Kalteng Pos. This study aims to see how the strategies and models of media convergence are carried out by Kalteng Pos along with the elements of the media's political economy. This research uses descriptive qualitative method with data collection in the form of interviews, observations, and literature studies. The findings of this study are Kalteng Pos in its media convergence adopts the convergence continuum model, newsroom convergence model, and content convergence model. Then in relation to the political economy of the media, there are elements of commodification, spatialization, and structuration in media convergence from Kalteng Pos.